Identity management : a business perspective - Williamson, Graham (MC Press Online, LLC, 2017)
For business managers and CIOs, managing identity data of employees, contractors, business partners, and customers has become an important core capability. This practical guide discusses the impacts of identity management on organizations from a businessperson's perspective.